How Perceived Security Influences Continuance Intention to Use Mobile Wallet - Aprilia, Cut; Amalia, Rizki (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2022)
This study's primary goal is to examine the effect of perceived security on mobile wallet users’ continuance intention using the Cognitive Model. A survey was conducted, and 230 responses from mobile wallet users were collected through the distribution of online-questionnaire. The data was analyzed using Partial Least Square- Structural Equation Model (PLS-SEM). This study revealed that perceived security directly correlates with satisfaction and attitude but not with users’ continuance intention. However, perceived safety still has a critical role in users’ decision to continue using the mobile wallet since this study found that satisfaction and attitude lead to users’ continuance intention. Moreover, happiness is also the predictor of users’ perspectives.